Penguatan Peraturan Desa (Perdes) Berbasis Kearifan Lokal Dalam Pengelolaan dan Perlindungan Hutan di Desa Tanjung Mudo - Harmaini, Harmaini; Dahri, Muhtar; Chandra, Febrian; Salman; Wulansari, Ditya Putri; Wati, Ica Karina Ramadania; Nurhayati (PT. Meja Ilmiah Publikasi, 2026)
Tanjung Mudo Village has abundant forest resources and inherits local wisdom values in maintaining its ecosystem. However, environmental degradation and the influx of external influences threaten forest sustainability and dilute these traditional values. This community service activity aims to strengthen the capacity of village officials and the community in establishing legal instruments in the form of Village Regulations (Perdes) on Forest Management and Protection based on local wisdom. The method used is Participatory Action Research (PAR) through the stages of socialization, Focus Group Discussion (FGD), legal drafting assistance, and public testing of the draft Perdes. The results of the service showed an increase in village officials' understanding of harmonizing national regulations with customary law. The resulting draft Perdes includes conservation zoning, prohibition of illegal logging, utilization of non-timber forest products, and the application of customary sanctions integrated legally and formally. In conclusion, strengthening village legal products that accommodate local wisdom has proven effective in empowering the community while ensuring sustainable protection of natural resources, creating a strong synergy between positive law and local community traditions